Possibilities for Growing Switch-grass (Panicum virgatum) as Second Generation Energy Crop in Dry-subhumid, Semiarid and Arid Regions of the Argentina - Falasca, Silvia Liliana (2017)
Panicum virgatum (swich-grass) is cultivated in some countries to obtain biomass used in the production of heat, fiber, electricity and second generation ethanol. Currently, in Argentina, this species is used for forage and as an ornamental. The aim of this work was to design an agroclimatic zoning model for swich-grass in Argentina, both for upland and lowland ecotypes, based on its bioclimatic requirements and employing a Geography Information System. The variables taken into consideration were: average temperature during growing period and reproductive period, frost free days and rainfall during growing season. This work demonstrated that an ample region of the country is agro-climatically suitable for the implantation of switch-grass in rainfed conditions or with complementary irrigation. The agroclimatic zoning for the upland ecotype shows that suitability reaches latitudes of up to 46ºS, while the lowland ecotype can be grown up to 40ºS. Thornthwaite's Moisture Index equal to zero was overlapped to the Argentinean agroclimatic zoning for upland and lowland types, to obtain the potential growing areas under dry-subhumid, semiarid to arid climates. The areas where switch-grass should be effectively tested are those categorized as optimal, very suitable, suitable, and very suitable/suitable with irrigation, located to the West of TMI equal to zero, which include dry-subhumid (0<TMI<-20), semiarid (-20<TMI<-40) and arid (-40<TMI<-60) climates. This agroclimatic zoning model can be applied to any region in the world, using the same bioclimatic indices and the classes delimited in this paper.